2017
DOI: 10.1002/14651858.cd010770.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Selective progesterone receptor modulators (SPRMs) for uterine fibroids

Abstract: Short-term use of SPRMs resulted in improved quality of life, reduced menstrual bleeding and higher rates of amenorrhoea than were seen with placebo. Thus, SPRMs may provide effective treatment for women with symptomatic fibroids. Evidence derived from one RCT showed no difference between leuprolide acetate and SPRM with respect to improved quality of life and bleeding symptoms. Evidence was insufficient to show whether effectiveness was different between SPRMs and leuprolide. Investigators more frequently obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 64 publications
1
37
0
2
Order By: Relevance
“…Other SPRM members such as mifepristone, asoprisnil, vilaprisan and telapristone acetate have been investigated in phase 2 clinical trials with promising preliminary results. 18,25 A main concern for all progesterone-inhibiting agents is the potential for induced endometrial growth by the unopposed estrogens, which could lead to the development of endometrial hyperplasia/cancer, although not confirmed by clinical trials, and other non-malignant reversible histological findings. 24 For this reason, their long-term treatment safety profile is still under investigation.…”
Section: Selective Progesterone Receptor Modulators and Anti-progesmentioning
confidence: 99%
“…Other SPRM members such as mifepristone, asoprisnil, vilaprisan and telapristone acetate have been investigated in phase 2 clinical trials with promising preliminary results. 18,25 A main concern for all progesterone-inhibiting agents is the potential for induced endometrial growth by the unopposed estrogens, which could lead to the development of endometrial hyperplasia/cancer, although not confirmed by clinical trials, and other non-malignant reversible histological findings. 24 For this reason, their long-term treatment safety profile is still under investigation.…”
Section: Selective Progesterone Receptor Modulators and Anti-progesmentioning
confidence: 99%
“…As a class, the SPRMs have been shown to be effective for improving QoL, decreasing menstrual blood loss, and achieving amenorrhea. 9 There have been 2 randomized trials evaluating asoprisnil from 5-20 mg per day. These studies showed that asoprisnil is able to suppress uterine bleeding in a dosedependent manner in patients with UF.…”
Section: The Pastmentioning
confidence: 99%
“…[2][3][4] The majority of women remain largely asymptomatic; however, they can cause debilitating symptoms in up to 30%. 3 Clinical features range from heavy menstrual bleeding to pain, pressure and subfertility, with symptom severity often depending on the number and position of the fibroids.…”
Section: Historical Perspectivementioning
confidence: 99%
“…2 Furthermore, the use of UPA as postulated would potentially open a new frontier for the medical management of uterine fibroids. This will be in line with other gynaecological disorders, for example, ectopic pregnancy where management has gone from a purely surgical intervention to 30% of women being managed medically.…”
Section: The Futurementioning
confidence: 99%